mTOR/α-ketoglutarate signaling: impact on brain cell homeostasis under ischemic conditions - Lushnikova, Iryna; Kostiuchenko, Olha; Kowalczyk, Magdalena; Skibo, Galyna (Frontiers in Cellular Neuroscience, 2023)
The multifunctional molecules mechanistic target of rapamycin (mTOR) and α-ketoglutarate (αKG) are crucial players in the regulatory mechanisms that maintain cell homeostasis in an ever-changing environment. Cerebral ischemia is associated primarily with oxygen-glucose deficiency (OGD) due to circulatory disorders. Upon exceeding a threshold of resistance to OGD, essential pathways of cellular metabolism can be disrupted, leading to damage of brain cells up to the loss of function and death. This mini-review focuses on the role of mTOR and αKG signaling in the metabolic homeostasis of brain cells under OGD conditions. Integral mechanisms concerning the relative cell resistance to OGD and the molecular basis of αKG-mediated neuroprotection are discussed. The study of molecular events associated with cerebral ischemia and endogenous neuroprotection is relevant for improving the effectiveness of therapeutic strategies.